Der lange Schatten des >Roten Oktober< Zur Relevanz und Rezeption sowjet-russischer Kunst, Kultur und Literatur in Österreich 1918-1938 - Kucher, Primus-Heinz; Unterberger, Rebecca (Peter Lang International Academic Publishers, 2019)
The book focuses on the reception relations of Soviet Russian art, culture and literature in Austria from 1918 to 1938. It shows their resonance, locating it in discourses typical of the time such as activism, New Objectivity, avantgarde of theatre and music, but also contemporary American discourse.